Structural response for stochastic kinematic interaction. - Hadid, Mohamed (Earthquake engineering & structural dynamics.)
The influence of stochastic kinematic interaction (SKI) on structural response is investigated in this paper. The SKI is evaluated through a computational model based on the boundary element method (BEM) formulated in the frequency domain. The singular integrals required in the computation of BEM are evaluated in a closed form. It is assumed that the foundation input motion (FIM) is the result of the superposition of many plane, stationary, correlated stochastic SH-, P- and SV waves travelling within a homogeneous viscoelastic soil at different angles. The results obtained indicate that the effect of SKI on the foundation response is qualitatively similar to that of wave passage. Both effects involve a reduction of translational components of the response at intermediate and high frequencies and creation of a rotational response component at intermediate frequencies, which decreases at high frequencies. While, it is found that the SKI decreases the maximum response of structures built on embedded rigid strip foundations excited by SH and P waves, it increases the maximum response for SV waves, except when the natural frequency of the structure is less than 0.5 Hz and for short structures excited by shallowly incident SV waves.